Answer:
The solution is x=1,y=2,z=3
Explanation:
The given system of equations is ;\
2x−3y+4z=8...(1)
3x+4y−5z=−4...(2)
4x−5y+6z=12...(3)
Make x the subject in equation (1)
![x=(8+3y-4z)/(2)...(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ykmv7jv3n70zmlpp5gxxtfz3acltgnkwx3.png)
Put equation (4) into equation (2) and (3)
![3((8+3y-4z)/(2))+4y-5z=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zpi1txfy1xo3h0kuhwrfyav2cjpan1tsv0.png)
Multiply through by;
![3(8+3y-4z)+8y-10z=-8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j2w72jlk3tzt4d64fand8hoah0serlgouo.png)
Expand;
![24+9y-12z+8y-10z=-8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hulpxk2afv7pum6pk8kzzggf472cyfwsp6.png)
Simplify;
![17y-22z=-32...(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/usei98dlgemw482tsda0tv237xnh81ldcl.png)
Equation (4) in (3)
![4((8+3y-4z)/(2))-5y+6z=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2stkors6jtg28bgy4w61ffv0z54qyz8hgs.png)
![2(8+3y-4z)-5y+6z=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cnlu9ksme82zwmkcjhe010e2y3emdatpuz.png)
![16+6y-8z-5y+6z=12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nw1emyyhda5qelf7e9queb5zgzgfvpsepm.png)
![y-2z=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m0du7huqs6veub8lczngt6dzpsws6wyerx.png)
![y=2z-4...(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gp3gx3bavh6bybcluaa1bn8qwuavx903de.png)
Put equation (6) into equation (5)
![17(2z-4)-22z=-32](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jjv5t3uh9w2yhqr5os85l80o3vhq7fn3ik.png)
![34z-68-22z=-32](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tw4wtuf30pob9k4hwqbn4ysss8tsybu5si.png)
![34z-22z=-32+68](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oqcyi2of2f8ontxyh1307pdknwz7amg9s1.png)
![12z=36](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n5ocrlx2owdasbwrb3g42ecklzn7hgbrig.png)
z=3
Put z=3 into equation (6)
y=2(3)-4=2
Put y=2 and z=3 into equation 4
![x=(8+3(2)-4(3))/(2)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mp9du8r188rk5wpqajzutkmimrarxf82i9.png)
The solution is x=1,y=2,z=3